Analysis of the metering performance for typical shape maize seeds using DEM - Shi, Linrong; Zhao, Wuyun; Sun, Wei; Yang, Xiaoping; Wang, Guanping; Xin, Shanglong (International Journal of Agricultural and Biological Engineering, 2023)
The irregular shape, varying internal compositions, and uneven distributions of maize seeds can degrade the metering performance of maize seeders. This study investigates the effect of irregular maize on the performance of a high-filling-rate seed metering device using DEM. The results show that the seed population in the seed box formed large and small cycles of seed transport due to the disturbances caused by the three wheels. The increasing angular speed of the three wheels reduced the rate of seed filling in the seed filling regions by gravity and disturbances. In addition, an analysis of the repose angle formed by the dropped seed indicated that the angular speed of the taking seed wheel has a certain effect. The large angular speed reduced the coefficient of variation of the seed drop location. The repose angle of the horse tooth seed was greater than those of the other. Meanwhile, the irregular maize seed can also reduce the coefficient of variation of the seed drop location. A comparison between the simulation and experiment results indicates the number of metering seed were basically the same. Keywords: maize seeds, seed metering performance, DEM, verification DOI: 10.25165/j.ijabe.20231601.6813 Citation: Shi L R, Zhao W Y, Sun W, Yang X P, Wang G P, Xin S L. Analysis of the metering performance for typical shape maize seeds using DEM. Int J Agric & Biol Eng, 2023; 16(1): 26–35.